Supramolecular micelles as multifunctional theranostic agents for synergistic photodynamic therapy and hypoxia-activated chemotherapy. (1st September 2021) - Huang, Xiaobei; Chen, Tunan; Mu, Ning; Lam, Hou Wang; Sun, Chen; Yue, Ludan; Cheng, Qian; Gao, Cheng; Yuan, Zhen; Wang, Ruibing
Abstract: Photodynamic therapy (PDT), where a photosensitizer (under light irradiation) converts molecular oxygen to singlet oxygen to elicit programmed cell death, is a promising cancer treatment modality with a high temporal and spatial resolution. However, only limited cancer treatment efficacy has been achieved in clinical PDT due to the hypoxic conditions of solid tumor microenvironment that limits the generation of singlet oxygen, and PDT process often leads to even more hypoxic microenvironment due to the consumption of oxygens during therapy. Herein, we designed novel supramolecular micelles to co-deliver photosensitizer and hypoxia-responsive prodrug to improve the overall therapeutic efficacy. The supramolecular micelles (CPC) were derived from a polyethylene glycol (PEG) system dually tagged with hydrophilic cucurbit[7]uril (CB[7]) and hydrophobic Chlorin e6 (Ce6), respectively on each end, for synergistic antitumor therapy via PDT of Ce6 and chemotherapy of a hypoxia-responsive prodrug, banoxantrone (AQ4N), loaded into the cavity of CB[7]. In addition, CPC was further modularly functionalized by folate (FA) via strong host-guest interaction between folate-amantadine (FA-ADA) and CB[7] to produce a novel nanoplatform, AQ4N@CPC-FA, for targeted delivery. AQ4N@CPC-FA exhibited enhanced cellular uptake, negligible cytotoxicity and good biocompatibility, and improved intracellular reactive oxygen species (ROS) generation efficiency. More importantly, in vivo evaluation of AQ4N@CPC-FA revealed a synergistic antitumor efficacy between PDT of Ce6 and hypoxia-activated chemotherapy of AQ4N (that can be converted to chemotherapeutic AQ4 for tumor chemotherapy in response to the strengthened hypoxic tumor microenvironment during PDT treatment). This study not only provides a new nanoplatform for synergistic photodynamic-chemotherapeutic treatment, but also offers important new insights to design and development of multifunctional supramolecular drug delivery system. Statement of significance: Photodynamic therapy (PDT) has exhibited a variety of advantages for cancer phototherapy as compared to traditional chemotherapy. However, the unsatisfactory therapeutic efficacy by PDT alone as a result of the enhanced tumor hypoxia during PDT has limited its clinical application. Herein, we designed multifunctional supramolecular micelles to co-deliver photosensitizer and hypoxia-responsive prodrug to improve the overall therapeutic efficacy. The supramolecular micelles are biocompatible and possess strong red absorption, controlled drug release profile, and ultimately enhanced therapeutic outcome via PDT-chemotherapy. This study not only provides a new nanoplatform for synergistic photodynamic-chemotherapeutic treatment of cancer, but also offers important new insights to design and development of multifunctional supramolecular drug delivery tool for multi-modality cancer therapy. Graphical abstract: Image, graphical abstract